Toxic Relationship: Recognizing, Realizing, and Handling IT - Resekiani Mas Bakar; Rifky Nurhidayat; Nur Halimah; Nafisah Amalia; Virginia Maharani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Toxic relationship behavior is often found in society due to relationships that are not good for oneself and others. This psychoeducation is carried out with the aim of providing the public with knowledge regarding toxic relationships. The number of participants was 15 people. Understanding is measured by giving a pre-test and post-test. The data analysis technique in this research uses the gain score test and t-test which aims to test changes in participants' level of understanding. The pre-test and post-test results from participants showed a Sig value. amounting to 0.000, thus indicating that there is a significant impact on the psychoeducational activities carried out